Comportamentos e valores informacionais no cenário brasileiro de crise sanitária durante a pandemia de COVID-19 - Christine Conceição Gonçalves (2023)
The existence of increasingly intense flows of information in all areas of individual, organizational and social enterprises requires the improvement of skills and abilities that make it possible to access and use information to make health decisions effectively and respond to daily demands in the face of uncertainties and needs for change. This study describes and analyzes health informational behaviors and values in the Brazilian health crisis scenario during the COVID-19 pandemic; and explains the sources of information used in this context. The Information Orientation (IO) model developed by Donald A. Marchand, William J. Kettinger and John D. Rollins was used as a theoretical basis for this study, complemented by Savolainen's model Everyday Life Information Seeking - ELIS, Taylor's Information Use and Choo's Information Use. The OI model has as its central components information technology practices, information management and informational behaviors and values. For the development of this research, characterized as quantitative-qualitative of an applied nature, it focused on the component ‘informational behaviors and values’. Data collection was carried out through a questionnaire sent via an Internet link to Brazilian individuals who use virtual media and social networks; and was complemented with semi-structured interviews, allowing the explanation of sources and channels of information used during the COVID-19 pandemic. To examine the data obtained from the application of the questionnaire, descriptive statistics were used to analyze the means between the variables, as well as explore the relationship between the variables of the seven dimensions studied in this research: proactive information use, transparency and formality as to the use of information, integrity, sharing, monitoring and use of health information. T-statistic tests were performed to describe associations between variables from information sources and identify differences between men and women regarding health informational behaviors and values. Chi-square tests (x2) were performed to analyze the differences between the percentages in the degrees of relevance and trust attributed to the information sources. The data obtained from interviews were transcribed and analyzed by breaking the text down into analogically grouped categories so as to help understanding the discourses. Results show that the health informational behaviors and values of the research participants, as well as the multiple sources of information used by them: digital media; traditional media; institutional sources; scientific sources; specialists in the areas of Health Sciences, Biological Sciences and related areas; personal sources and information multiplier agents. Among the seven dimensions of informational behaviors and values, there was a predominance of information integrity, use of information and proactive information use.